Association Between Medication Adherence and Oxidative Stress in Patients With First-Episode Mania - García, Saínza; Alberich, Susana; MacDowell, Karina S.; Martínez-Cengotitabengoa, Mónica; López, Purificación; Zorrilla, Iñaki; Leza, Juan Carlos; González-Pinto, Ana (Frontiers in Psychiatry, 2019)
Poor adherence is a major problem in patients with manic episodes that impairs functionality and has unknown effects on oxidative stress. The objective of this study was to analyze the relationship between adherence to medication, severity of symptoms and oxidative stress in a sample of patients with a first episode of mania. A longitudinal, 6-month study was performed in 60 patients, who were classified as adherent and non-adherent to medication (mainly antipsychotics). Blood levels of oxidative stress parameters and expression of the antioxidant nuclear transcription factor NRF2 in mononuclear cells of peripheral blood were assessed at baseline and at the end of follow-up. In addition, clinical symptoms and functioning were evaluated. Linear multivariate regression was used to determine the relationship between adherence, oxidative stress, and clinical symptoms. Finally, 44 patients completed follow-up. The results of this study showed that at 6-month follow-up, adherence was significantly associated with better functioning and reduced clinical symptoms. Additionally, more severe symptoms were associated with increased levels of oxidative stress and antioxidant parameters. At study completion, non-adherents exhibited greater levels of antioxidants than adherent patients. In conclusion, poor adherence to medication is associated with a poorer prognosis in the medium term and causes increased antioxidant response.